Experimental study on railway vehicle lateral performance under different lateral disturbance - Abdullah, Mohd Azman; Ahmad, Fauzi; Harun, Mohd Hanif; Mohamed Jamil, Fathiah; Ibrahim, Munaliza; Ubaidillah, Ubaidillah (Semarak Ilmu Publishing, 2024)
Railway systems are integral to modern transportation, connecting regions and facilitating the movement of goods and passengers. One critical aspect of railway performance is the lateral dynamics, influenced by various external disturbances. In this study, an experiment was carried out to investigate the lateral performance of railway vehicles subjected to different lateral disturbances. The research utilizes an experimental approach and analytical tools to comprehensively analyze the effects of lateral disturbances on railway performance. The double-acting pneumatic actuator was used which acts as lateral disturbance with the five different pressures. Then, the accelerometer sensor was used to record the motion of the railway vehicle including track, bogie, and body, and the data was analyzed in MATLAB software. The primary objectives are to quantify the dynamic responses of railway vehicles under these disturbances and assess the impact on lateral acceleration. Comprehensive data analysis provides insights into the behaviors of railway vehicles in real-world scenarios. Results from this study show high force lateral disturbances can trigger dynamic responses in the train system. This may include swaying, hunting oscillations, or wheel unloading, all of which can affect the overall performance and stability of the train. The lateral acceleration increases when the lateral disturbance increases. Therefore, disturbance contributes to a deeper understanding of lateral dynamics in railway systems, aiding in the development of robust control systems.